Fasciola hepatica juveniles interact with the host fibrinolytic system as a potential early-stage invasion mechanism. - Judit Serrat; David Becerro-Recio; María Torres-Valle; Fernando Simón; María Adela Valero; María Dolores Bargues; Santiago Mas-Coma; Mar Siles-Lucas; Javier González-Miguel (Public Library of Science (PLoS), 2023)
Background The trematode Fasciola hepatica is the most widespread causative agent of fasciolosis, a parasitic disease that mainly affects humans and ruminants worldwide. During F. hepatica infection, newly excysted juveniles (FhNEJ) emerge in the duodenum of the mammalian host and migrate towards their definitive location, the intra-hepatic biliary ducts. Understanding how F. hepatica traverses the intestinal wall and migrates towards the liver is pivotal for the development of more successful strategies against fasciolosis. The central enzyme of the mammalian fibrinolytic system is plasmin, a serine protease whose functions are exploited by a number of parasite species owing to its broad spectrum of substrates, including components of tissue extracellular matrices. The aim of the present work is to understand whether FhNEJ co-opt the functions of their host fibrinolytic system as a mechanism to facilitate trans-intestinal migration. Methodology/principal findings A tegument-enriched antigenic extract of FhNEJ (FhNEJ-Teg) was obtained in vitro, and its capability to bind the zymogen plasminogen (PLG) and enhance its conversion to the active protease, plasmin, were analyzed by a combination of enzyme-linked immunosorbent, chromogenic and immunofluorescence assays. Additionally, PLG-binding proteins in FhNEJ-Teg were identified by bidimensional electrophoresis coupled to mass spectrometry analysis, and the interactions were validated using FhNEJ recombinant proteins. Conclusions/significance Our results show that FhNEJ-Teg contains proteins that bind PLG and stimulate its activation to plasmin, which could facilitate the traversal of the intestinal wall by FhNEJ and contribute to the successful establishment of the parasite within its mammalian host. Altogether, our findings contribute to a better understanding of host-parasite relationships during early fasciolosis and may be exploited from a pharmacological and/or immunological perspective for the development of treatment and control strategies against this global disease.